Positive CMR findings are associated with polymorphic ventricle arrhythmias and ECG repolarization changes but not with exercises induced arrhythmias in competitive and non-competitive athletes. (11th May 2022) - Penza, M; Filomena, D; Monosilio, S; Birtolo, L; Serdoz, A; Lemme, E; Squeo, M; Mango, R; Di Gioia, G; Fedele, F; Gualdi, G; Spataro, A; et al.
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Cardiac magnetic resonance (CMR) provides an effective contribution for the prevention of sudden cardiac death with its ability to provide accurate information on morpho-functional abnormalities and on myocardial tissue characterization. However, data on its utility in clinical scenario in the competitive athletes are limited to selected cohort of patients with complex arrhythmias. Objective: To retrospectively analyze all the CMR performed at our center for evaluating the predictors of positive CMR findings in a large cohort of competitive and non-competitive athletes presenting with different clinical indications. Methods: Over a period of 30 months all the CMR performed on athletes aged > 14 years and training for at least 5 hours per week at our Institutes were retrospectively recruited. The following data were also collected: medical history, ECG, echocardiography, exercise testing. CMR were categorized as "positive" or "negative" based on the presence or absence of late gadolinium enhancement (LGE, excluding RV insertion point) and/or morphological and/or functional abnormalities. Predictors of "positive" CMR were explored. Results: 503 CMR were recruited and the most frequent indications for CMR were: ventricular arrythmias (n= 213, 42%), ECG abnormalities (n= 140, 28%) followed by echocardiogram abnormalities, symptoms and family history (Figure A). 308 (61%) CMR were "negative" and 195 (39%) "positive" (Figure B). Uncommon ventricular arrythmias did not result associated with positive CMR (p= 0.43), while polymorphic ventricular beats are associated with positive CMR (p= 0.02). Among ECG abnormalities only T-waves inversion, particularly on lateral and infero-lateral leads, were associated with positive CMR (p= 0.04). Conclusion: Ventricular arrhythmias represented the most common indication for require a CMR but in almost half the cases, the CMR was negative. Excises induced ventricular arrhythmias is not significantly associated with pathological findings on CMR, while the polymorphic morphology of arrhythmias and the presence of lateral and infero-lateral repolarization abnormalities on ECG were associated with positive CMR.